PENGEMBANGAN HANDBOOK STRATEGI PEMBELAJARAN INOVATIF UNTUK MENINGKATKAN KOMPETENSI GURU HOMESCHOOLING DI KOTA BANDUNG [THE DEVELOPMENT OF AN INNOVATIVE LEARNING STRATEGY HANDBOOK TO IMPROVE THE COMPETENCE OF HOMESCHOOLING TEACHERS IN BANDUNG CITY] - Jeremy, Edsel; Winardi, Yonathan (Polyglot, 2025)
Homeschooling is increasingly popular as an alternative educational model, but it faces challenges, including the need for competent teachers who can cater to diverse student needs. This study aimed to develop and evaluate a competency development program for homeschooling teachers in Bandung City, packaged as a handbook titled "Strategi Pembelajaran Inovatif" (Innovative Learning Strategies). The research utilized a Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate). The Define stage involved a Focus Group Discussion (FGD) with homeschooling leaders and interviews with teachers, revealing a need for enhanced teacher competency, particularly in innovative learning strategies. The Design stage focused on creating the handbook structure and content, covering "Mengenal Homeschooling" (Understanding Homeschooling) and "Strategi Pembelajaran Inovatif," which includes personalized learning, project-based learning, inquiry-based learning, and technology integration. The Develop stage included expert validation (content, design, technology) which rated the handbook favorably (average scores 2.8, 2.9, and 2.9 out of 3, respectively, leading to minor revisions) and a trial with homeschooling teachers. The trial showed an increase in participants' understanding, with average pre-test scores of 61.17 and post-test scores of 70.75. Feedback on the training program and handbook was generally "good" (average rating 83.77). The Disseminate stage involved distributing the handbook to four other homeschooling institutions in Bandung, which provided "sufficient" feedback (average rating 75/100) and positive impressions. The study concludes that the developed handbook is a viable and relevant tool for enhancing the competencies of homeschooling teachers in Bandung. Abstrak Bahasa Indonesia Homeschooling semakin diminati sebagai model pendidikan alternatif, namun menghadapi berbagai tantangan, termasuk kebutuhan akan guru yang kompeten dan mampu melayani kebutuhan siswa yang beragam. Penelitian ini bertujuan untuk mengembangkan dan mengevaluasi program pengembangan kompetensi bagi guru homeschooling di Kota Bandung, yang dikemas dalam bentuk sebuah handbook berjudul "Strategi Pembelajaran Inovatif". Penelitian ini menggunakan metode Penelitian dan Pengembangan (R&D) dengan model 4D (Define, Design, Develop, Disseminate). Tahap Define melibatkan Focus Group Discussion (FGD) dengan pimpinan homeschooling dan wawancara dengan guru, yang mengungkap kebutuhan peningkatan kompetensi guru, khususnya dalam strategi pembelajaran inovatif. Tahap Design berfokus pada perancangan struktur dan konten handbook, yang mencakup materi "Mengenal Homeschooling" dan "Strategi Pembelajaran Inovatif" (pembelajaran personalisasi, project-based learning, inquiry-based learning, dan integrasi teknologi). Tahap Develop meliputi validasi ahli (konten, desain, teknologi) yang menilai handbook secara positif (rata-rata skor 2,8, 2,9, dan 2,9 dari 3, yang mengarah pada revisi minor) dan uji coba kepada guru homeschooling. Hasil uji coba menunjukkan peningkatan pemahaman peserta, dengan skor rata-rata pre-test 61,17 dan post-test 70,75. Umpan balik terhadap program pelatihan dan handbook umumnya "baik" (rata-rata penilaian 83,77). Tahap Disseminate melibatkan pendistribusian handbook ke empat institusi homeschooling lain di Kota Bandung, yang memberikan umpan balik "cukup" (rata-rata penilaian 75/100) dan kesan positif. Penelitian ini menyimpulkan bahwa handbook yang dikembangkan merupakan alat yang layak dan relevan untuk meningkatkan kompetensi guru homeschooling di Kota Bandung.